The Importance of the Mubāsyarah Method in Arabic Language Instruction - Ahmad Mutahar; Affan Maula Utsman; Abdul Rozak Alawi; Ahmad Abdul Hafiz; Hidayatullah; Athiyyatul Maula; Inda Iswatin; Baiq Eka Sabrina Hafsari; Karnika (Formad English Foundation NTB-Jakarta, 2026)
Arabic language instruction continues to face challenges in developing students’ communicative competence, particularly when teaching practices rely heavily on translation and grammatical explanations rather than active language use. In response to this issue, communicative teaching approaches such as the Mubāsyarah Method (Direct Method) have gained increasing attention in Arabic language pedagogy. This study aims to examine the importance of the Mubāsyarah Method in Arabic language instruction by analyzing its conceptual foundations, its contributions to the development of students’ Arabic language skills, and its pedagogical implications for effective language teaching. The research employed a qualitative literature review approach by analyzing scholarly articles, books, and academic publications related to the Mubāsyarah Method and Arabic language teaching published within the last ten years. Data were collected through systematic literature searching and document analysis, and the selected sources were analyzed using qualitative content analysis to identify key themes and patterns in previous studies. The findings indicate that the Mubāsyarah Method plays a significant role in promoting communicative Arabic language learning by emphasizing the direct use of the target language in classroom interaction. The method contributes to the development of students’ speaking and listening skills, contextual vocabulary acquisition, and grammatical understanding through meaningful communication. In addition, the interactive learning environment created by the method enhances students’ motivation, confidence, and engagement in language learning. The study also highlights important pedagogical implications for Arabic language teaching, including the adoption of communicative and student-centered learning strategies, the importance of teacher competence, and the development of supportive language environments. Overall, the Mubāsyarah Method provides an effective framework for improving the quality and effectiveness of Arabic language instruction.